Neural network control of a robot manipulator - Liew, Kang Chew. (2009)
A robot manipulator moves under applied forces and torques coupled with a specific set of dynamic equations. The inverse dynamic equations of a manipulator specify the necessary forces and torques for generating a desired motion. Therefore, we can apply the desired position, velocity and acceleration of the manipulator to the inverse dynamic equations to determine the forces and torques required to obtain this motion [2].